Leptin and ghrelin concentrations and eating behaviors during the early and late luteal phase in women with premenstrual dysphoric disorder. (August 2020) - Yen, Ju-Yu; Lin, Huang-Chi; Lin, Pai-Cheng; Liu, Tai-Ling; Long, Cheng-Yu; Ko, Chih-Hung
Highlights: Women with PMDD exhibited higher body mass index (BMI), early-luteal (EL) & late-luteal (LL) leptin levels. They increased leptin, sweet cravings, and uncontrolled eating from EL to LL phase. PMDD women with higher BMI increased more in leptin. Depression mediated the association between PMDD and uncontrolled eating. They exhibit higher depression and emotional eating, which positively correlated with their higher BMI in LL phase. Abstract: Objectives: In this study, we evaluated the changes in leptin and ghrelin concentrations, eating behavior, depression, and impulsivity and their correlations within the luteal phase among women with premenstrual dysphoric disorder (PMDD). Methods: In 63 women with PMDD and 53 healthy controls, we prospectively evaluated serum levels of leptin and ghrelin, Body Mass Index(BMI), and self-reported sweet cravings, cognitive restraint, uncontrolled eating, emotional eating, depression, and impulsivity during the early luteal (EL) and late luteal (LL) phases. Results: Compared with the controls, the women with PMDD had higher BMI, higher leptin concentrations in the EL and LL phase, and leptin concentrations increased from the EL to the LL phase. However, there is no significant difference in ghrelin. Women with PMDD increased sweet cravings and uncontrolled eating from EL to LL phase. No significant correlation was observed between the EL-LL changes in leptin or ghrelin concentrations and those in eating behaviors. Both depression and impulsivity correlated with sweet craving and uncontrolled eating. Depression mediated the association between PMDD and uncontrolled eating. The BMI of women with PMDD positively correlated with their EL-LL change in leptin, and LL depression levels and emotional eating. Conclusion: Young women with PMDD had higher leptin concentrations and BMI in the luteal phase. The LL leptin level was not the primary factor responsible for the increased uncontrolled eating of PMDD. Whether the increased eating and depression in the LL phase contribute to the risk of obesity or hyperleptinemia among women with PMDD need to be evaluated in the future.